Refining the phenotype associated with GNB1 mutations: Clinical data on 18 newly identified patients and review of the literature. Issue 11 (8th September 2018) - Hemati, Parisa; Revah‐Politi, Anya; Bassan, Haim; Petrovski, Slavé; Bilancia, Colleen G.; Ramsey, Keri; Griffin, Nicole G.; Bier, Louise; Cho, Megan T.; Rosello, Monica; Lynch, Sally Ann; Colombo, Sophie; et al.
Abstract : De novo germline mutations in GNB1 have been associated with a neurodevelopmental phenotype. To date, 28 patients with variants classified as pathogenic have been reported. We add 18 patients with de novo mutations to this cohort, including a patient with mosaicism for a GNB1 mutation who presented with a milder phenotype. Consistent with previous reports, developmental delay in these patients was moderate to severe, and more than half of the patients were non‐ambulatory and nonverbal. The most observed substitution affects the p.Ile80 residue encoded in exon 6, with 28% of patients carrying a variant at this residue. Dystonia and growth delay were observed more frequently in patients carrying variants in this residue, suggesting a potential genotype–phenotype correlation. In the new cohort of 18 patients, 50% of males had genitourinary anomalies and 61% of patients had gastrointestinal anomalies, suggesting a possible association of these findings with variants in GNB1 . In addition, cutaneous mastocytosis, reported once before in a patient with a GNB1 variant, was observed in three additional patients, providing further evidence for an association to GNB1 . We will review clinical and molecular data of these new cases and all previously reported cases to further define the phenotype and establish possible genotype–phenotype correlations.